Effects of Allium sativum extract in arsenic induced toxicity in Swiss albino mice - Adhara, Rusafa Antashin (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.